2011
DOI: 10.1002/cyto.b.20603
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric characterization of cerebrospinal fluid cells

Abstract: Flow cytometry facilitates the detection of a large spectrum of cellular characteristics on a per cell basis, determination of absolute cell numbers and detection of rare events with high sensitivity and specificity. White blood cell (WBC) counts in cerebrospinal fluid (CSF) are important for the diagnosis of many neurological disorders. WBC counting and differential can be performed by microscopy, hematology analyzers, or flow cytometry. Flow cytometry of CSF is increasingly being considered as the method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
115
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 115 publications
4
115
0
4
Order By: Relevance
“…As discussed above, the potential usefulness of flow cytometric immunophenotyping in detecting leptomeningeal involvement by aggressive B-cell non-Hodgkin lymphomas is well established (1)(2)(3)(4)(5). However, the cases presented here suggest that in patients without an established diagnosis of lymphoma, the detection of a B-cell population with monotypic light chain expression in CSF by polychromatic flow cytometry is not, in isolation, diagnostic of occult leptomeningeal involvement by lymphoma, and highlight the importance of clinicopathologic correlation in this application of polychromatic flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, the potential usefulness of flow cytometric immunophenotyping in detecting leptomeningeal involvement by aggressive B-cell non-Hodgkin lymphomas is well established (1)(2)(3)(4)(5). However, the cases presented here suggest that in patients without an established diagnosis of lymphoma, the detection of a B-cell population with monotypic light chain expression in CSF by polychromatic flow cytometry is not, in isolation, diagnostic of occult leptomeningeal involvement by lymphoma, and highlight the importance of clinicopathologic correlation in this application of polychromatic flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…In these and other studies (reviewed in 4,5), flow cytometry of CSF has been shown to be substantially more sensitive than conventional cytologic examination in identifying involvement by lymphoma. Moreover, one of the anticipated advantages of polychromatic flow cytometry, which has become increasingly common in the clinical laboratory, is the ability to detect rare populations defined by multiple parameters in paucicellular specimens (6)(7)(8).…”
mentioning
confidence: 88%
“…[43][44][45][46][47] The use of flow cytometry in detecting CNS-MM has so far been limited to few reported cases, as shown in our review of the literature. We think that the application of flow cytometry in cases of multiple myeloma, suspected for CNS involvement, should be encouraged with the aim of improving the clinical diagnostic strategy and establishing both the most useful MoAb panels and the most specific gating strategy, giving great attention to possible artifacts, as suggested by recent data by Craig et al 48 Finally, a precocious diagnosis of CNS-MM, especially when MRI results to be negative, might be very important to design therapeutic strategies in this setting of patients.…”
mentioning
confidence: 89%
“…Major concerns with this procedure are the loss of cells during centrifugation [96,102], aberrant cell morphology due to the forces of centrifugation [103], and clustering of macrophages or mesothelial cells (which can be mistaken for malignancy, especially in the case of pleural effusions and ascites fluids) [104]. To overcome these difficulties, studies recommend specimens to be fresh and processed within a few hours to limit cellular degradation [103], immediate addition of a serum contaning medium to CSF tubes to protect against degradation and cellular distortion [105], and to carefully validate centrifugation speed and processing time because these can influence the quality of the slide [104].…”
Section: Manual Microscopymentioning
confidence: 99%